Development of Natural Preservative from Silene vulgaris Extract in Topical Formulation under a Challenge Test and its Stability Stud - Smahane BOUKHIRAa, Mounyr BALOUIRIb, Latifa El MANSOURIa, Amal El HAMSAS El YOUBIa, Mouna BOUARFAa, Siham LEBTARa, Ahmed OUHAMMOUc, Dalila BOUSTAa (Journal of Applied Pharmaceutical Science, 2017)
The development of natural preservatives provides a way of substituting or decreasing the amount of synthetic preservatives normally used in pharmaceutical and cosmetic products. The purpose of this research was to evaluate the Silene vulgaris extract efficiency as a natural preservative in topical cream formulation. The antimicrobial activity of S. vulgaris extract was assayed for determination of the minimum inhibitory concentration. The in-vitro stability was studied for the cream formulation stored at different temperatures 4°C, 25°C and 37 °C. However the effectiveness of antimicrobial effect of extracts at concentrations (2-20%) in topical cream was assayed by using a microbial challenge test. This test was performed following the standard procedure proposed by The European Pharmacopoeia, using reference strains: Staphylococcus aureus ATCC 29213, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, Candida albicans ATCC 10231 and Aspergillus brasiliensis ATCC 16404. The results demonstrated that S. vulgaris extract at10% and 20% (w/w) reduced the bacteria and fungi inocula, according to the criterion A of the European Pharmacopoeia, with a significant conservation during a period of 28 days compared to phenoxyethanol as a synthetic preservative. Our study indicate that under the tests conditions, Silene vulgaris extract has antimicrobial activity and could be considered as an alternative preservative for cosmetic formulations.
Keywords: Challenge test, reservatives, Silene vulgaris, cosmetic microbiological stability.